2019
DOI: 10.3389/fonc.2019.00895
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Based Prognostic Analysis of Cell-in-Cell Structures in Early Breast Cancer

Abstract: Though current pathological methods are greatly improved, they provide rather limited functional information. Cell-in-cell structures (CICs), arising from active cell–cell interaction, are functional surrogates of complicated cell behaviors within heterogeneous cancers. In light of this, we performed the subtype-based CIC profiling in human breast cancers by the “EML” multiplex staining method, and accessed their values as prognostic factors by Cox univariate, multivariate, and nomogram analysis. CICs were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…Durgan et al (22), and our unpublished work as well, identified cell division as a potent inducer of entotic CIC formation, the mechanism might also work in this case as the tumor cells are undergoing active division as indicated by >70% Ki-67 positivity. A review of the limited literature on CIC formation in breast cancer (Table 1) showed that CIC structures were also frequently associated with active cell proliferation (3,22,24) and, to an extent, cellular heterogeneity (15,16,24,25); and the frequencies of CIC structure, although difficult to compare due to the different types of calculation, span a wide range from presence (24,25,27) to 6% in this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Durgan et al (22), and our unpublished work as well, identified cell division as a potent inducer of entotic CIC formation, the mechanism might also work in this case as the tumor cells are undergoing active division as indicated by >70% Ki-67 positivity. A review of the limited literature on CIC formation in breast cancer (Table 1) showed that CIC structures were also frequently associated with active cell proliferation (3,22,24) and, to an extent, cellular heterogeneity (15,16,24,25); and the frequencies of CIC structure, although difficult to compare due to the different types of calculation, span a wide range from presence (24,25,27) to 6% in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Cell cannibalism is a unique pathological phenomenon that has been observed in various types of human tumors, including breast cancer (1). Cannibalistic cells typically form cellin-cell (CIC) structures, characterized by enclosure of cells by another one, and this affects patient prognosis (2,3). CIC structures have not only been found in human tumors but also in animal tumors (4), suggesting that CIC is a general malignant phenomenon across species.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-in-cell (CIC) is an evolutionarily conserved cytobiological phenomenon ( 1 , 2 ), which was first reported 150 years ago by a German scholar ( 3 ). It refers to the presence of one or more living cells within another living one and has ever since been found in varieties of tumors tissues, such as breast carcinoma ( 4 , 5 ), pancreatic ductal adenocarcinoma ( 6 ), and head and neck squamous cell carcinoma (HNSCC) ( 7 ) and the like. CIC has two typical forms: one is homotypic CIC, and the other is heterotypic CIC, with the latter often occurring between tumor cells and immune cells that include neutrophils ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of cannibalistic cell-in-cell structures has been reported in many cancers as an adverse prognostic feature [16,19,20]. Cellular cannibalism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the cell-in-cell structure has been wellknown for decades among pathologists, but its clinical significance has remained neglected. Only recent research has emphasized the significance of the cell-in-cell phenomenon in the behavior of many cancers [15][16][17]. However, the clinical relevance of cell-in-cell has not been well-studied in many cancers of the head and neck region including early OTSCC.…”
Section: Introductionmentioning
confidence: 99%